The SDSS-V Local Volume Mapper: Data Analysis Pipeline - Sánchez, Sebastian F.; Mejía-Narváez, Alfredo; Egorov, Oleg; Kreckel, Kathryn; Drory, Niv; Blanc, Guillermo A.; Méndez-Delgado, José Eduardo; Barrera-Ballesteros, Jorge K.; Ibarra-Medel, Hector; Bizyaev, Dmitry; García, Pablo; Wofford, Aida; et al. (The astronomical journal, 2025)
We introduce the data analysis pipeline (DAP) for the Sloan Digital Sky Survey V Local Volume Mapper (LVM) project, referred to as the LVM-DAP. We outline our methods for recovering both stellar and emission-line components from optical integral field spectroscopy, highlighting the developments and changes implemented to address specific challenges of the data set. The observations from the LVM project are unique because they cover a wide range of physical resolutions, from approximately 0.05 pc to 100 pc, depending on the distance to the target. This, along with the varying number of stars sampled in each aperture (ranging from zero, just one to a few, to thousands), presents challenges in using previous spectral synthesis methods and interpreting the spectral fits. We provide a detailed explanation of how we model the stellar content and separate it from the ionized gas emission lines. To assess the accuracy of our results, we compare them with both idealized and more realistic simulations, highlighting the limitations of our methods. We find that the DAP robustly corrects for stellar continuum features and recovers emission-line parameters (e.g., flux, equivalent width, systemic velocity, and velocity dispersion) with precision and accuracy that fulfill the requirements of the primary goal of the analysis. In addition, the recovered stellar parameters are reliable for single stars, while the recovery of integrated populations is less precise. We conclude with a description of the data products we provide, instructions for downloading and using our software, and a showcase illustrating the quality of the data and the analysis on a deep exposure taken on the Huygens region at the center of the Orion Nebula.